The Effect of the Teaching Campus Program on Students' Literacy and Numeracy Skills - Fathul Rahman; Fathahillah; Nurul Mukhlisah Abdal (PT. Global Research Collaboration, 2026)
The purpose of this study was to analyze the effect of the campus teaching program on literacy skills and to analyze the effect of the campus teaching program on the numeracy skills of students at SMP Negeri 52 Makassar. This study was a descriptive quantitative study. The data collection instruments used were tests consisting of pre-tests and post-tests, interviews, and documentation. The sample in this study consisted of 35 eighth-grade students at SMP Negeri 52 Makassar. The results obtained from this study are (1) The teaching campus program has a fairly effective influence (62%) on literacy skills. The t-test results show a sig p<0.001 value, which is smaller than sig p<0.05, meaning that there is an influence of the teaching campus program on the literacy skills of students at SMP Negeri 52 Makassar. (2) The teaching campus program had a fairly effective influence (53%) on numeracy skills. The t-test results showed a sig p<0.001 value, which is smaller than p<0.05, meaning that the teaching campus program had an influence on the numeracy skills of students at SMP Negeri 52 Makassar. Based on this data, it can be concluded that the campus teaching program has a positive effect on students' literacy and numeracy skills.